Comparison of open, flexible, and enclosed learning spaces – teaching staff’s experiences and activity sound exposure - Radun, Jenni; Keränen, Jukka; Rantanen, Sanna; Veermans, Marjaana; Hongisto, Valtteri (Elsevier BV, 2025)
Learning spaces can be categorized into open, flexible, and enclosed spaces. Enclosed space enables teaching one 20–30 students’ group while open space enables teaching several groups in the space simultaneously. Flexible spaces offer a possibility for closing and opening the space. This study examined whether teaching staff’s experience and sound exposure differ in learning space types. The questionnaire responses from primary schools’ teaching staff working in enclosed space (enclosed environment group, N = 267) were compared with teaching staff working in flexible or open spaces (innovative environment group, N = 94) (total N = 361). Additionally, the activity sound pressure levels (SPLs) were measured in 20 schools’ four learning spaces for five workdays. The innovative environment group was less satisfied with sound environment, amount of space, functionality of transit routes and more disturbed by environmental factors than the enclosed environment group. Almost a third (29 %) of the innovative environment group perceived that their learning space did not support the pedagogical methods they wanted to use, while this was 15 % in the enclosed environment group. The learning environment groups did not differ in noise annoyance related to different places in school, nor the prevalence of vocal symptoms. The activity SPLs in the open learning spaces were lower or similar than in the enclosed learning spaces but did not differ between enclosed and flexible learning spaces. Negative experience in innovative learning environments is not related to higher noise levels, but to environmental distractions, therefore, open learning spaces’ design should always consider cognitive ergonomics along with action possibilities.